2013
DOI: 10.1002/ajhb.22440
|View full text |Cite
|
Sign up to set email alerts
|

Socio‐demographic and behavioral risk factors associated with the high prevalence of overweight and obesity in portuguese children

Abstract: Objectives Childhood obesity is a public health concern in Portugal. Socio‐demographic and behavioral factors are highly associated with obesity but are not clearly understood. This article aims to update the prevalence of overweight and obesity in Portuguese children and to explore the influence and risks of socio‐demographic factors and behavioral factors. Methods A cross‐sectional study of Portuguese children aged 3–10 years from all 18 mainland districts took place between March 2009 and January 2010. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
55
0
8

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 45 publications
3
55
0
8
Order By: Relevance
“…Numerous studies [4,7,8,14,15,25,27,56] have sought to highlight the factors playing a major role in this relationship. Understanding these factors will help to devise and implement focused preventive measures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous studies [4,7,8,14,15,25,27,56] have sought to highlight the factors playing a major role in this relationship. Understanding these factors will help to devise and implement focused preventive measures.…”
Section: Discussionmentioning
confidence: 99%
“…Several systematic reviews and observational studies have suggested an effect of breastfeeding on the risk of childhood overweight/obesity and adiposity [16][17][18][19][20][21][22][23][24][25]. Many prospective studies have found a positive association between poor childhood dietary habits and body weight in later life [26,27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, those differences did not remain significant when comparing overweight and obesity separately. Differences among genders have been observed in previous studies but are not consistent with some registering higher levels of overweight/obesity among girls than boys 3,34 while others found the inverse. 15,17,36 These disparities between studies may be due to differences in age groups or lifestyle habits (e.g., physical activity and diet).…”
Section: Discussionmentioning
confidence: 49%
“…33 Later, in 2008, 37.9% children living in Portugal were classified as overweight (including obese) and 15.3% obese, 14 and a study carried in 2009/2010 among 9 -10-year-old Portuguese children observed that 31% of the children were overweight/obese. 34 More recently, data from the central region of Portugal, observed that among 6 -12-year-old children, 22.3% were considered overweight and 10.7% as obese. 17 Those results, compared with the prevalence found in this study for overweight (15.9%), obesity (6.1%) and overweight including obesity (21.9%), suggest that the prevalence of overweight and obesity may have been decreasing in the last few years.…”
Section: Discussionmentioning
confidence: 99%